"Just hanging with my friends": U.S. Latina/o/x perspectives on parasocial relationships in podcast listening during COVID-19. (2nd October 2022) - Soto-Vásquez, Arthur D.; Vilceanu, M. Olguta; Johnson, Kristine C.
ABSTRACT: There is a need to delve into major subgroups among U.S. Latina/o/xs and identify emerging patterns in their understanding and consumption of new media. This study used six small-group interviews to explore the fluidity of parasocial dynamics with podcasts among young Latina/o/x podcast listeners experiencing the COVID-19 lockdown. Recent literature has focused on the parasocial nature of dynamics, relationships, and emotional connections listeners develop with their favorite podcasts. While we found that there are unique circumstances of listening among young Latina/o/x listeners, such as living with family and working during school, their podcast interests are driven by identification with hosts, age, and gender more than ethnic parameters. The conceptual acronym EASY (Engaged Experience, Accessible Authenticity, Socialization in Solitude, and Youth and YouTube) was developed to interpret pandemic listening among Latina/o/x podcast users.